Fracture performance of a PCM-Rich concrete pavement under thermal stresses. Issue 2 (28th January 2022) - Sharifi, Naser P.; Askarinejad, Sina; Mahboub, Kamyar C.
ABSTRACT: Curling stresses in rigid pavements are the result of temperature gradient through the thickness of the concrete slab. These stresses have a periodic nature, and the induced cyclic flexural curling stresses lead to the cracking of the concrete slab. In a previous research by the authors, a phase change material (PCM)-rich concrete overlay was proposed as an effective method to control this failure mechanism. A PCM-rich concrete overlay is a concrete surface layer that contains a relatively high percentage of PCM. In the previous study, a phenomenological approach was employed, and it was demonstrated that the incorporation of PCM improves the curling fatigue performance of the concrete slab. Using fracture mechanics, this paper builds upon the findings of the previous study, and it serves as a mechanistic verification of the conclusions of the previous work. A modified Paris' Law was adopted to calculate the cumulative fatigue-fracture damage of the concrete slab due to cyclic thermally-induced curling stresses. The findings of this research demonstrated that the PCM-modified concrete slab undergoes a curling-induced fracture process that is less severe than the slab without the PCM. The impact of this reduction was quantified in terms of an improved fatigue-fracture performance of the pavement.